Human polyomaviruses JCPyV and MCPyV in urothelial cell carcinoma: a single institution experience - Klufah, Faisal; Mobaraki, Ghalib; Shi, Shuai; Marcelissen, Tom; Alharbi, Raed A.; Mobarki, Mousa; Almalki, Shaia Saleh R.; van Roermund, Joep; zur Hausen, Axel; Samarska, Iryna (Frontiers in Oncology, 2023)
Urothelial cell carcinoma (UCC) is the most common malignancy type of urinary bladder. JCPyV and BKPyV have been detected in the urine and tissue of urothelial cell carcinomas (UCC) in immunocompetent patients. Here, we investigated the presence of several HPyVs in UCC samples using diverse molecular techniques to study the prevalence of HPyVs in UCC.A large single-institution database of urine cytology specimens (UCS; n= 22.867 UCS) has previously been searched for Decoy cells (n= 30), suggesting polyomavirus infection. The available urine sediments and formalin-fixed paraffin-embedded (FFPE) tissue samples of UCC patients were tested for the presence of JCPyV-LTAg expression by immunohistochemistry (IHC) labeled with SV40-LTAg antibody (clone: PAb416) and subsequent PCR followed by sequencing. In addition, the presence of the oncogenic Merkel cell polyomavirus (MCPyV) and the presence of human polyomavirus 6 and 7 (HPyV6; HPyV7) DNA were tested with DNA PCR or IHC.Of the 30 patients harboring Decoy cells, fourteen patients were diagnosed with UCC of the urinary bladder (14/30; 46.6%) before presenting with Decoy cells in the urine. The SV40-LTAg IHC was positive in all fourteen UCC urine sediments and negative in the FFPE tissues. JCPyV-DNA was identified in all five available UCS specimens, and in three FFPE samples of UCC (3/14; 21.4%). Two UCC cases were positive for MCPyV DNA (2/14; 14.3%) and one of them showed the protein expression by IHC (1/14; 7.1%). All specimens were HPyV6 and 7 negative.Our findings show the presence of JCPyV in the urine and UCC of immunocompetent patients. Moreover, MCPyV was detected in two UCC cases. In total 5 UCC cases showed the presence of either JCPyV or MCPyV. The evidence here supports the hypothesis that these viruses might sporadically be associated with UCC. Further studies are needed to confirm the relevance of JCPyV or MCPyV as a possible risk factor for UCC development.